2007
DOI: 10.1158/0008-5472.can-06-4064
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I, Regulating Aromatase Expression through Steroidogenic Factor 1, Supports Estrogen-Dependent Tumor Leydig Cell Proliferation

Abstract: The aim of this study was to investigate the role of estrogens in Leydig cell tumor proliferation. We used R2C rat Leydig tumor cells and testicular samples from Fischer rats with a developed Leydig tumor. Both experimental models express high levels of aromatase and estrogen receptor A (ERA). Treatment with exogenous 17B-estradiol (E 2 ) induced proliferation of R2C cells and up-regulation of cell cycle regulators cyclin D1 and cyclin E, the expression of which was blocked by addition of antiestrogens. These … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 51 publications
5
69
0
Order By: Relevance
“…Aromatase transcription in Leydig cells is mainly controlled by transcription factors pCREB and SF-1. In a previous study (4) we showed that SF-1 transcriptional regulation is controlled by a transduction pathway that does not involve PKA directly. This indicates that, even in the presence of very low levels of pCREB, as is the case after treating cells with H89, SF-1 can still drive aromatase transcription maintaining the gene expression.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Aromatase transcription in Leydig cells is mainly controlled by transcription factors pCREB and SF-1. In a previous study (4) we showed that SF-1 transcriptional regulation is controlled by a transduction pathway that does not involve PKA directly. This indicates that, even in the presence of very low levels of pCREB, as is the case after treating cells with H89, SF-1 can still drive aromatase transcription maintaining the gene expression.…”
Section: Discussionmentioning
confidence: 91%
“…The relative gene expression levels were normalized to a calibrator that was chosen to be the basal, untreated sample. Final results were expressed as n-fold differences in gene expression relative to 18 S rRNA and calibrator, calculated following the ⌬⌬C t method, as published previously (4).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations